Handbook of research on consumerism in business and marketing concepts and practices - Kaufmann, Hans Rüdiger 1958- (Advances in marketing, customer relationship management and e-services (AMCRMES) book series, 2014)
"This book features research on diverse topics on consumerism in the global marketplace, focusing on the ways in which businesses can improve their relationships with customers as well as analyze and influence purchasing behavior"..